2009
DOI: 10.1007/s10803-009-0740-5
|View full text |Cite
|
Sign up to set email alerts
|

Global Visual Processing and Self-Rated Autistic-like Traits

Abstract: The current research investigated, firstly, whether individuals with high levels of mild autistic-like traits display a similar profile of embedded figures test (EFT) and global motion performance to that seen in autism. Secondly, whether differences in EFT performance are related to enhanced local processing or reduced global processing in the ventral visual stream was also examined. Results indicated that people who scored high on the Autism-spectrum Quotient (AQ) were faster to identify embedded figures, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 99 publications
8
104
1
Order By: Relevance
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 61%
“…One interesting direction for future research would be an investigation into the sensory processing of children with varying levels of autistic traits. Furthermore, it would be interesting to investigate whether the differences observed in those with high and low levels of autistic traits in behavioural studies (Grinter et al, 2009a;Grinter, 2009b;Stewart & Ota, 2008) and fMRI (Von dem Hagen, 2011) would also be found in children. In addition, it would be an important next step to determine whether self-reported sensory sensitivity actually corresponds to differences in threshold.…”
Section: Implications For Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Grinter et al (2009a) showed that performance on the Embedded Figures Test (EFT) and the Block Design component of the Weschler Intelligence Scale is positively related to AQ score (see also Almeida et al 2010). Grinter and colleagues also showed high performance in the EFT along with weak global form and motion detection (Grinter et al 2009b).…”
Section: Autistic Traits In the Typically Developed Populationmentioning
confidence: 99%
“…Children with autism differ from typically developing children across many domains, including local versus global processing style (Crespi and Badcock 2008;Grinter et al 2009;Russell-Smith et al 2010). Here, we focus on object analysis in terms of hidden figures.…”
Section: Introductionmentioning
confidence: 99%